Pengaruh Leverage dan Profitabilitas Terhadap Kebijakan Dividen dan Nilai Perusahan - Putra, I Wayan Juniastina; Wiagustini, Ni Luh Putu (E-Jurnal Manajemen; Vol 3 No 9 (2014), 2014)
The company needs sufficient funds to compete and maintain viability. Maximize firm value is one of company goals and to achieved that goal the company need to notice factors that affect the firm value. This research aimed to examine effect of leverage and profitability on dividend policy and firm value. This research was conducted at consumer goods industry on Indonesian Stock Exchange with 15 companies obtained as sample and determined by purposive sampling method. Analysis technique used in this research was path analysis. Based on results analysis it was found that, leverage significant positive effect on profitability, leverage significant negative effect on dividend policy, profitability significant positive effect on dividend policy, leverage insignificant negative effect on firm value, profitability significant positive effect on firm value  and dividend policy significant positive effect on firm value. Keywords: leverage, profitability, dividend policy, firm value